Business feasibility analysis of quail cattle (Cortunix japonica) in quinsha farm. Issue 1 (March 2021) - Zainal,; Tandi, Ismail; Juwita, Sartika; Darma, R
Abstract: Quail is one of the livestock that is easily cultivated and has advantages, namely high egg, and meat production and a short and easy maintenance period. Another feature of quail is that it has a short life cycle, a small body that does not require a large space. The purpose of this study was to determine the feasibility of the quail laying business of Quinsha Farm (Takalar Quail House) in terms of economic aspects. The research method used is descriptive research method by analyzing the quail farm business directly in Quinsha Farm (Takalar Quail House). The results of the study of business feasibility analysis at Quinsha Farm (TakalarQuail House) are an Investment Cost of Rp. 98, 000, 000 - production costs Rp. 262, 252, 000 - receipts of Rp. 576, 900, 000 -, profits, Rp. 281, 253, 536 - R/C Ratio 1.95 B/C Ratio of 0.95 ROI of 46.20% BEP Price of Rp. 16, 667 - BEP Production of 9, 855 Shelves and PBP 6.27 Months. The conclusion of this Business Analysis Study is the laying quail farming business in Quinsha Farm (Takalar Quail House) that is profitable and feasible to develop.